Pirataria de audiovisual : o protocolo BitTorrent como forma extraoficial de distribuição online de longas-metragens - Furini, Liana Gross (2015)
This dissertation aims the analysis of the non-official practices of distribution of feature length films. Although piracy follows the cinematographic industry since its beginning, the popularization of digital technologies has contributed to the increase of the discussions on the subject. In this work, we used the Grounded Theory and will analyze the user s interaction with the piracy to understand their responsibility related to the non-official distribution of cinematographic material. We applied the analysis in two feature length films, focusing on BitTorrent protocol: Let The Right One In (2008) and Captain America: The Winter Soldier (2014). We realized with these analyzes, that the unofficial distribution is more agile than the formal distribution, attracting spectators and creating new demands for the industry. We emphasize that the computer and the internet are key-piece in the increase of official circulation. The computer, for the ability to produce many copies in a short time, and the Internet for the possibility of distributing the content worldwide at no cost and with great agility.